INTEGRASI PROTOKOL MQTT DAN HTTP UNTUK OTOMASI BERBASIS IOT PADA PERTANIAN LAHAN KERING - Hendro FJ Lami; Kalvein R Rantelobo; Jani F Mandala; Agistinus S Sampeallo (Universitas Nusa Cendana, 2020)
The availability of telecommunication infrastructure and services has not been evenly distributed throughout the NTT region. This problem becomes the basis of this research to develop a communication system that capable of reaching areas without a telecommunications network. Through the LORA gateway on the raspberry pi, information from areas that are not covered by telecommunications services is sent to another gateway using a working frequency of 915MHz. The plant in this study is the regulation of soil moisture with the input of 2 sensors and 1 relay for controlling land irrigation activities. An esp8266 sensor node collects the sensing results of the YL-69 and DS18B20 sensors to control the pump motor operation. The process of sending data between the sensor node and the gateway uses the mqtt protocol. Users in areas served by the internet network can access all published data on the test website. The results of controlling the plant area in the test area fluctuated and tended to be stable at between 60% and 80%.